Diversity in Grain, Flour, Amino Acid Composition, Protein Profiling, and Proportion of Total Flour Proteins of Different Wheat Cultivars of North India - Siddiqi, Raashid Ahmad; Singh, Tajendra Pal; Rani, Monika; Sogi, Dalbir Singh; Bhat, Mohd Akbar (Frontiers in Nutrition, 2020)
Wheat cultivars grown at three different locations in North India were assessed for their variability in kernel and flour characteristics. Protein and the wet and dry gluten contents of the flour varied significantly (p ≤ 0.05) from 9.32 to 12.60%, 23.46 to 43.04%, and from 8.28 to 15.00%, respectively. Wheat varieties exhibited moderate sodium dodecyl sulfate (SDS) sedimentation and solvent retention values. Flour showed a significant (p ≤ 0.05) difference in the amino acid composition. Lysine, having the lowest chemical score, was the first most limiting amino acid in all wheat varieties. The variability of total flour proteins determined by SDS-PAGE showed polymorphism both in the number and intensity of bands, particularly in the molecular weight range of 35.1–42.8 kDa corresponding to the α-, β-, and γ-gliadin/low-molecular-weight glutenin subunit (LMW-GS) region. Pearson's correlation established between the various grain and flour parameters showed a significant correlation, which can result in better end product use.